SmartPresence: Wi-Fi-based online attendance management for smart academic assistance - Mijanur Rahaman; Md. Masudul Islam; Dip Nandi (Journal of Electrical Systems and Information Technology)
Abstract SmartPresence, a Wi-Fi-based attendance management system marks a significant leap in evaluating student performance, replacing traditional manual methods with pen-and-paper timesheets or paper-based student signatures. This innovative system utilizes smartphones and Wi-Fi signals, allowing students to connect their devices to a designated router upon entering the classroom for attendance registration. The captured data is stored centrally, instantly notifying both administrators and teachers in real time. This approach not only revolutionizes attendance tracking but also enhances overall classroom management by leveraging Wi-Fi-enabled devices like smartphones and laptops. This system introduces a progressive solution, utilizing contemporary connectivity for a seamless and intelligent attendance monitoring experience for educators and students alike.